Answer:
The correct answer is (FALSE)
Step-by-step explanation:
(APEX)
Writing the two equations in full and subtracting R(x) from W(x) to arrive at D (x) gives the answer. This is shown below;
W(x) = 0.002x^3 - 0.01x^2 + 0x + 0
R (x) = 0x^3 + x^2 - 4x +13 -
-----------------------------------------------
D(x) = 0.002x^3 -1.01x^2 + 4x - 13
You multiply it together like (a+b)(a+b)
the answer would be a^2 + 2ab + b^2
Answer:
x = 2/5
Step-by-step explanation:
Given:
7 + 5x = 3(y-2)
Rearrange this equation such that x is expressed in terms of y
7 + 5x = 3(y-2) (expand right side)
7 + 5x = y(3)-2(3)
7 + 5x = 3y-6 (subtract 7 from both sides)
5x = 3y - 6 - 7
5x = 3y - 13
we are given the y-value of the coordinate pair (? , 5)
simply substitute y=5 into the equation above
5x = 3y - 13
5x = 3(5) - 13
5x = 15 - 13
5x = 2 (divide both sides 5)
x = 2/5
Answer:A true
Got it right in the odyssey ware
Step-by-step explanation: